Assessing the Influence of Vegetation on the Water Budget of Tropical Areas. Issue 5 (2018) - Casagrande, Enrico; Recanati, Francesca; Melià, Paco
Abstract: The regulation of the water cycle is a major service provided by forests. However, this service is endangered by the deforestation taking place in areas like the Brazilian Amazon basin. In this study, we use two different approaches to investigate how evapotranspiration and rainfall partitioning are influenced by different vegetation covers (forest and pasture). We first explore a dataset produced with a global model (GLEAM) and compare its predictions with those obtained with an existing simulation software (HYDRUS 1-D). Both methods consistently show that forests guarantee higher evapotranspiration rates than pastures, thus providing a larger contribution to water-related ecosystem services.